ELECTRIC DRIVES IN EXISTING ELECTRIC MOTORS RU SEC UML. ENERGY PARAMETERS OF THE ENGINE TO DISPLAY ENERGY SAVING MEASURES - Xolliyev Jovohir; Amrullayev Behzod; Kamolov Bekzot (Galaxy International Interdisciplinary Research Journal, 2022)
The article contains comparative descriptions of asynchronous electric motors of power lines in in-dustrial enterprises with a lot of details about the internal supply of washers in textile inventory and energy-saving measures of rotary motors.